Enhancing the competitiveness of agricultural commodity chains in Nigeria - Liverpool-Tasie, Lenis Saweda; Ayoola, Gbolagade B.; Oyeleke, Razaq O. (International Food Policy Research Institute, 2010)
Nigeria's economic performance since 2002 has improved, with growth averaging about 7.3 percent during 2002-07 (Global insight 2008). While the production of cassava, rice, and maize has responded to the associated improved policy incentives in recent years, factors such as poor infrastructure and limited market outlets have served as great disincentives to farmers. Using household data in a "Policy Analysis Matrix" (PAM) framework, the comparative advantage of Nigerian farmers in producing cassava, rice, and maize in high potential states, given current national policies, is examined.